Treatment with a macrolide-containing regimen for Mycobacterium kansasii pulmonary disease. (March 2019) - Moon, Seong Mi; Choe, Junsu; Jhun, Byung Woo; Jeon, Kyeongman; Kwon, O Jung; Huh, Hee Jae; Lee, Nam Yong; Daley, Charles L.; Koh, Won-Jung
Abstract: Background: Mycobacterium kansasii is a major pathogen associated with nontuberculous mycobacterial pulmonary disease. For treatment of M. kansasii pulmonary disease, daily therapy with isoniazid, rifampin, and ethambutol is traditionally recommended. Although a regimen containing a macrolide, instead of isoniazid, has been recently recommended, supporting data are limited. We compared the treatment outcomes of a macrolide-containing regimen (macrolide group) and an isoniazid-containing regimen (isoniazid group) on patients with M. kansasii pulmonary disease. Methods: A total of 49 patients were identified between January 2002 and December 2016. Treatment outcomes for the isoniazid group (n = 24) and the macrolide group (n = 25) were compared. Results: Baseline characteristics of the isoniazid and macrolide groups were similar. Favorable outcomes did not differ between the isoniazid group (79%, n = 19) and macrolide group (88%, n = 22, P  = 0.463). Total treatment duration (median 17.9 months vs. 15.4 months; P  = 0.712) and time to culture conversion (median 2.0 months vs. 1.2 months; P  = 0.838) were also similar between the isoniazid and macrolide groups. Five patients who completed three-times-weekly intermittent treatment containing a macrolide for non-cavitary M. kansasii pulmonary disease achieved negative sputum culture conversion within 12 months of treatment. Only one patient experienced recurrence of M. kansasii pulmonary disease in the isoniazid group. Conclusions: A macrolide-containing regimen appears to be as effective as an isoniazid-containing regimen for treatment of M. kansasii pulmonary disease. Additionally, intermittent therapy containing a macrolide could be an alternative treatment option for non-cavitary M. kansasii pulmonary disease.